Pengembangan Media Augmented Reality dengan Unity 3D dan Vuforia Untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik Kelas X IPS SMA Negeri 7 Surakarta - Mawaddah Arrahmah; Singgih Prihadi; Sugiyanto Sugiyanto (GEADIDAKTIKA, 2025)
This study aims to: (1) identify the level of students’ needs for Augmented Reality (AR) learning media on the topic of Potential, Distribution, and Utilization of Inland Waters in Class X Social Science students of SMA Negeri 7 Surakarta; (2) determine the feasibility of AR-based media development for the same topic; and (3) assess the effectiveness of AR media in improving students’ creative thinking skills. The research employed a Research and Development (R&D) approach using the Four-D (4D) model, which includes the stages of Define, Design, Develop, and Disseminate. Data were collected through questionnaires, interviews, documentation, and tests, while data analysis was conducted by comparing pretest and posttest results. The findings reveal that: (1) students’ need for AR media was identified through a needs analysis that examined indicators such as creative thinking ability, learning media preferences, and learning styles; (2) AR media was deemed feasible for classroom use, supported by high validation scores from material and media experts, as well as positive responses from small- and large-group trials; and (3) AR-based learning effectively enhanced students’ creative thinking, demonstrated by a significant increase in average posttest scores compared to pretest results.